La universidad y el poder en el Perú: los últimos cien años - Lynch, Nicolás (2021)
This article addresses the counterpoint between the university and political power in Peru during the last hundred years. This power dispute, in the best and worst sense, will determine the course of this relationship. The university, mainly the public university, tries to position itself as a democratizing factor in the country while state power embraces changing attitudes: repression, abandonment, and privatization, to tame the rebellious and questioning impulses of university professionals. We analyze this issue focusing on the Universidad Nacional Mayor de San Marcos, considering its tradition, importance, leadership, and decline. It is an unresolved counterpoint that continues among the many questions about the future of Peruvian democratization.